Plan de negocios para la elaboración del yogurt con endulzante natural en el cantón Latacunga, provincia de Cotopaxi, Ecuador. - Castelo Torres, Andrea Jimena (2019)
Developing a business plan for the creation of a company that produces and commercializes yogurt with natural sweetener was the main of this research. Firstly, a market study was carried out that allowed the evaluation of the potential introduction of the goods at Latacunga city. Secondly, the financial viability of the future company was analyzed. In third place, the operative viability was analyzed, which served to measure the time that the company will take in each process for the goods elaboration. As a conclusion it can be affirmed that there is a potential market for the sale of the product; that there is financial viability to create the future company; and that the operations of goods elaboration are feasible in the proposed times. That is why, can be stated with propriety that the needs of a potential yoghurt consuming clientele can be met, with an added value "stevia" natural sweetener.